2017
DOI: 10.3892/etm.2017.4548
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-125b is associated with poor prognosis and trastuzumab resistance in HER2-positive gastric cancer

Abstract: Gastric cancer is one of the most common types of human cancer associated with a poor prognosis. MicroRNAs (miRs), a class of non-coding RNAs that are 18–25 nucleotides in length, act as key regulators in gene expression, and have been implicated in various human cancer types. miR-125b has been implicated in the malignant progression of gastric cancer. However, the association between miR-125b expression, clinicopathological characteristics and trastuzumab resistance in human epidermal growth factor receptor 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…We also compared our findings to studies evaluating miRNAs as predictive biomarkers in other types of cancers. In HER2‐positive gastric cancer, Sui et al has demonstrated that increased miR‐125b level in tumor tissue was significantly associated with trastuzumab resistance, advanced malignant progression, as well as poor prognosis. In vitro studies revealed that miR‐21/PTEN and miR‐223/FBXW7 pathways might be implicated in sensitivity of gastric cancer to trastuzumab .…”
Section: Discussionmentioning
confidence: 99%
“…We also compared our findings to studies evaluating miRNAs as predictive biomarkers in other types of cancers. In HER2‐positive gastric cancer, Sui et al has demonstrated that increased miR‐125b level in tumor tissue was significantly associated with trastuzumab resistance, advanced malignant progression, as well as poor prognosis. In vitro studies revealed that miR‐21/PTEN and miR‐223/FBXW7 pathways might be implicated in sensitivity of gastric cancer to trastuzumab .…”
Section: Discussionmentioning
confidence: 99%
“…7 Some experiments have shown that certain miRNAs, including miR-25, miR-20a, and miR-623 are associated with a poor prognosis of cancer and have been reported to be signicantly upregulated in recurrent gastric carcinoma. [8][9][10][11][12] Therefore, we hypothesized that gastric cancer resistance may be related to abnormal expression of miRNAs. In addition, a lot of evidence has revealed that miRNA is involved in gastric cancer initiation and progression, including MDR.…”
Section: Introductionmentioning
confidence: 99%
“…Through inhibiting PTEN expression, oncogenic miR-21 has been found to confer trastuzumab resistance in HER2-positive gastric cancer cells [154]. MiR-125b, which is markedly upregulated in gastric cancer tissues, is significantly associated with trastuzumab resistance and poor prognosis in HER2-positive gastric cancer patients [155]. Similarly, oncogenic miR-223 could decrease trastuzumab sensitivity of gastric cancer through suppressing expression of FBXW7 [156].…”
Section: Mirnas and Resistance To Targeted Therapy Drugsmentioning
confidence: 99%